2022
DOI: 10.1007/s00520-022-07301-1
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in terminally ill cancer patients: what is the role of using complementary and alternative medicines?

Abstract: Background and purpose Cancer is the world’s second greatest cause of mortality and a leading cause of death in both developed and developing countries. Patients employ a number of complementary and alternative medicine (CAM) methods to deal with the problems and difficulties of cancer, which can have an impact on their quality of life (QOL). The aim of the present study was to assess the correlation between QOL and the use of different CAM methods in terminally ill cancer patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 46 publications
4
9
0
Order By: Relevance
“…In Iran, gender, age, and economic status were associated with CAM use (34), suggesting that the use of CAM measures is in uenced by the cultural traditions of the region. Consistent with previous studies (33,35), we found that patients used different CAM measures, with natural products and mind-body practices as the most popular modalities.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In Iran, gender, age, and economic status were associated with CAM use (34), suggesting that the use of CAM measures is in uenced by the cultural traditions of the region. Consistent with previous studies (33,35), we found that patients used different CAM measures, with natural products and mind-body practices as the most popular modalities.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, we found that the main mind-body practices used by CKD patients were acupuncture and massage, whereas that used by cancer patients was spiritual therapy (33,35). Many cancer patients have late-stage disease and often opt for psychological reassurance (35), whereas CKD patients often require measures to treat somatic symptoms. Patients with CKD can have multiple co-morbidities, which may explain why they used CAM measures more often than conventional medicines to treat CKD.…”
Section: Discussionmentioning
confidence: 81%
“…The negative effects of COVID-19 on cancer patients, which are thought to continue for many years, are important. The use of effective coping mechanisms can reduce this psychological burden imposed on cancer patients [7] , [14] , [17] , [31] . CAM use is one of the coping methods commonly used by cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, the immune system of cancer patients can be suppressed due to the cancer and its treatment (e.g., chemotherapy) [1] , [2] , [3] , [4] . For these reasons, cancer patients are defined as a population at high-risk of poor COVID-19 outcomes [1] , [3] , [6] , [7] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation